COMMISSION CONTRACT IN CIVIL LEGISLATION OF THE REPUBLIC OF KAZAKHSTAN - Goryacheva , Елена Васильевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2017)
The legal nature and differential characteristic of the contract of commission in Kazakhstan's civil law is suggested in this article. Despite the presence of traditional norms about the commission in the civil law, the author believes that the Commission contract is poorly understood in the Kazakh legal literature and requires further research. A provisions of the Civil Code points out and describes by the author, that distinguish a modern regulation of the Commission in Kazakhstan. As the research task it was attempted to draw attention to a special position of the domestic legislator in some norms of the Commission bearing the controversial nature by the author. The need for change in wording of some articles of the Civil Code of the Commission was attempted to justify in the article. The article notes the positive approach taken by the legislator on the right of the commission to make the deal itself, as well as the right to a fee for the transaction itself. A Civil legislation of other CIS countries do not provide for a right to remuneration commission, which leads to litigation. Simultaneously, an article explains the need to change a wording of certain provisions of the Civil Code. Determination of the Commission subject of the contract is a prerequisite for its conclusion, as the only thing essential condition in this agreement, according to the author, some provisions of the Civil Code on the subject of the commission contract need to be improved. As a result of analysis, the author draws attention to the characteristics of the commission, allowing the treaty to include a group of business contracts. This article was prepared as part of the basic research of the Institute of Legislation of the Republic of Kazakhstan on the topic: "Actual problems and improvement of contractual obligations in civil legislation of the Republic of Kazakhstan: legal regulation, theory and practice".